Densitometric assessment of corneal transparency after correction of moderate myopia by femtosecond extraction of the lenticule through a small incision and using laser keratomilesis in situ with femtosecond assistance - O. V. Pisarevskaya (Офтальмохирургия, 2021)
Relevance. The study of the mechanisms of insufficiently rapid achievement of high visual acuity in the early postoperative period in the correction of myopia by the SMILE method is relevant. Purpose. To evaluate changes in corneal densitometry parameters after SMILE and FS-LASIK surgery in patients with moderate myopia. Material and methods. A study of 152 patients with moderate myopia was conducted, 68 were operated by SMILE and 84 – FS-LASIK. All procedures were performed using a VisuMax femtosecond laser and a MEL 80 excimer laser (Carl Zeiss Meditec, Germany). Assessment of visual acuity, corneal structure (OCT, Optovue, USA), corneal densitometry (Pentacam Scheimpflug, Germany) were performed before the operation, on the 1st, 5th day, 3, 6, 12 months after the operation. OCT scans were analyzed using the ImageJ program. Results. Оn the 1st day after SMILE, visual acuity (p=0.01) and transparency of the anterior and middle layers of the cornea were reduced than after FS-LASIK in the zone from 0 to 2 mm (p=0.045, p=0.001), from 2 to 6 mm (both p=0.001). These differences became statistically insignificant 5 days after surgery. By three and six months in the FS-ERASER group, the corneal transparency in the middle layers were reduced in the 0–2 mm and 2–6 mm zones (p=0.0001, p=0.001). In both groups, by 12 months, the corneal backscattering reached the values of the preoperative period (p>0,05). Conclusion. Refractive operations SMILE and FS-LASIK are accompanied by a decrease in corneal transparency, which is restored to preoperative values by 12 months. In the early postoperative period, an increase in densitometry indicators and a slower recovery of visual acuity after SMILE surgery may be due to active remodeling of the interface, which includes fragments of collagen fibrils and cellular components i nside the intrastromal space.